Pengembangan Wisata Budaya Berbasis Masyarakat di Desa Detusoko Kecamatan Detusoko Kabupaten Ende Nusa Tenggara Timur - Yoachim Rivaldo Watu Raka; Supri Hartono; Anggraeny Puspaningtyas (Jurnal Ilmu Pendidikan dan Sosial, 2023)
Tourism development is currently starting to become one of the leading programs in regional development. Tourism development is expected to be able to contribute to the receipt of regional original data collection and create regional cultural jobs. one of the Ende districts that has tourism potential is in the Detusoko sub-district. The tourism potential of Detusoko Village is a type of natural, cultural and artistic tourism of the Detusoko people with their uniqueness and character. One of the possible attractions of Detusoko Village is nature tourism, with mountains, hot springs, and rice fields surrounding Detusoko Village. In addition to nature tourism, there are cultural tours that introduce cultural elements and community customs. If managed properly, this cultural tourism area will make a significant contribution to Detusoko Village. This cultural tourism can be known from the location and cultural activities of Detusoko Village. B. Traditional houses and dances. Detusoko Tourism Village is one of the tourist villages in East Nusa Tenggara (NTT), namely Detusoko District, Ende Regency with a population of 211 heads of households, 758 residents with 362 male spirits and 396 female residents. This is a table of the population of the village of Detusoko.